x2+14×22=0

Multiply by 1.

x2⋅1+14×22=0

Factor x2 out of 14×22.

x2⋅1+x2(14×20)=0

Factor x2 out of x2⋅1+x2(14×20).

x2(1+14×20)=0

x2(1+14×20)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x2=0

1+14×20=0

Set the first factor equal to 0.

x2=0

Take the square root of both sides of the equation to eliminate the exponent on the left side.

x=±0

The complete solution is the result of both the positive and negative portions of the solution.

Simplify the right side of the equation.

Rewrite 0 as 02.

x=±02

Pull terms out from under the radical, assuming positive real numbers.

x=±0

x=±0

±0 is equal to 0.

x=0

x=0

x=0

Set the next factor equal to 0.

1+14×20=0

Subtract 1 from both sides of the equation.

14×20=-1

Divide each term by 14 and simplify.

Divide each term in 14×20=-1 by 14.

14×2014=-114

Cancel the common factor of 14.

Cancel the common factor.

14×2014=-114

Divide x20 by 1.

x20=-114

x20=-114

Move the negative in front of the fraction.

x20=-114

x20=-114

Take the 20th root of both sides of the equation to eliminate the exponent on the left side.

x=±-11420

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

x=-11420

Next, use the negative value of the ± to find the second solution.

x=–11420

The complete solution is the result of both the positive and negative portions of the solution.

x=-11420,–11420

x=-11420,–11420

x=-11420,–11420

The final solution is all the values that make x2(1+14×20)=0 true.

x=0,-11420,–11420

Solve using the Square Root Property x^2+14x^22=0